DIFFICULTIES IN SERVICE CROSS-CULTURAL COUNSELING IN THE KERINCI DISTRICT - Marjulis, Andini Fahira; Mumtaz Habibi, Farhan (Jurnal Kopendik, 2023)
Cross-cultural counseling poses various challenges that counselors must address to provide effective and beneficial counseling services to clients from different cultural backgrounds. These challenges include language and cultural differences that can affect communication and the quality of counseling, differences in values and beliefs that can influence how clients perceive issues and how counselors provide counseling, stereotypes and prejudices that can affect how counselors view their clients and the quality of counseling, gender role differences in different cultures that can affect the dynamics of counseling, and lack of cultural awareness that can affect counselors' ability to understand clients' cultures and provide effective counseling. The ineffectiveness of cross-cultural counseling can be caused by counselor factors, namely counselors who do not receive education/training and experience about cross-cultural counseling who are confined to their own culture. This is done to ensure that the counseling assistance provided is in accordance with the values and cultural norms adopted client.